Impacto de la diabetes, el sobrepeso y la obesidad en la calidad de vida relacionada con la salud del adolescente: Metanálisis (2015)
Diabetes mellitus and weight problems have negative clinical, epidemiological and economic consequences and deteriorate the Health Related Quality of Life (HRQoL) of adolescents.